2018
DOI: 10.1101/509216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synaptic vesicles transiently dock to refill release sites

Abstract: Synaptic vesicles fuse with the plasma membrane to release neurotransmitter following an action potential, after which new vesicles must refill vacated release sites. How many vesicles can fuse at a single active zone, where they fuse within the active zone, and how quickly they are replaced with new vesicles is not well-established. To capture synaptic vesicle exocytosis at cultured mouse hippocampal synapses, we induced single action potentials by electrical field stimulation then subjected neurons to high-p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(76 citation statements)
references
References 82 publications
(141 reference statements)
10
66
0
Order By: Relevance
“…Thus investigation of these AZ proteins may tell us localization, movement and regulation of DSs. In addition, nano-meter scale movements of synaptic vesicles have been observed after stimulation near the presynaptic membrane, indicating the speed and time course of vesicle recruitment (Midorikawa and Sakaba, 2015, 2017; Kusick et al, 2018). Those studies combined with the model simulation based on the quantal analysis may allow us to see the relationship between parameter values for predicted models and physical observations of DSs and synaptic vesicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus investigation of these AZ proteins may tell us localization, movement and regulation of DSs. In addition, nano-meter scale movements of synaptic vesicles have been observed after stimulation near the presynaptic membrane, indicating the speed and time course of vesicle recruitment (Midorikawa and Sakaba, 2015, 2017; Kusick et al, 2018). Those studies combined with the model simulation based on the quantal analysis may allow us to see the relationship between parameter values for predicted models and physical observations of DSs and synaptic vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed description of DS models by the developed method may more clearly define molecular/morphological correlates of synaptic parameters. In addition, nanometer-resolution observations in mammalian CNS using super-resolution imaging and electron microscopy have revealed synaptic vesicle movement in presynaptic terminals (Midorikawa and Sakaba, 2015, 2017; Rothman et al, 2016; Maschi and Klyachko, 2017; Chang et al, 2018; Kusick et al, 2018), and distribution of synaptic vesicles and AZ proteins (Siksou et al, 2007; Imig et al, 2014; Nakamura et al, 2015; Tang et al, 2016), paving the way for a comparison between data and DS model simulations for a comprehensive understanding of vesicle release/replenishment at DSs if the vesicle recruitment process and the pool size of releasable/suppliable vesicles can be predicted accurately by the new method.…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, distinct states of the active zone have been proposed to regulate neuronal communication by modulating synaptic vesicle positioning and release (Kittel and Heckmann, 2016). Within a given synapse, not all release sites are equally re-used during sustained synaptic activity (Kusick et al, 2020). The reduction in synaptic vesicles located at the active zone in Tau35 mouse brain may indicate disruption of synchronous vesicle release.…”
Section: Discussionmentioning
confidence: 99%
“…As detailed above, Doussau et al (2017) found evidence that the replenishment process is reversible on a slower time scale of ~200 ms. Interestingly, in a recent manuscript reporting results from electron microscopic analysis of hippocampal synapses, following stimulation and rapid freezing of cultured neurons, new SVs were recruited to the plasma membrane and fully replenished the docked pool of SVs within ~10 ms after stimulation (Kusick et al, 2018). The docking of these SVs was transient and they either undocked or fused within 100 ms.…”
Section: Parallel-fiber Synapsesmentioning
confidence: 99%